Perceptions and attitudes of users and non-users of mental health services concerning mental illness and services in Japan - Uchino, Takashi; Fukui, Eriko; Takubo, Youji; Iwai, Momoko; Katagiri, Naoyuki; Tsujino, Naohisa; Imamura, Haruhiko; Fujii, Chiyo; Tanaka, Kuniaki; Shimizu, Tetsuo; Nemoto, Takahiro (Frontiers in Psychiatry, 2023)
Objectives There is a global movement to develop and implement community-based integrated mental health systems. The present study attempted to clarify the perceptions and attitudes of users and non-users of mental health services concerning mental illness and services in Japan. Methods A new questionnaire was developed for this internet survey. Data from 500 outpatients with depression and 500 healthy subjects were sampled according to the demographics of the Japanese population. Results Over 90% of healthy subjects and over 70% of patients were unaware of the common age of onset or lifetime prevalence of mental illness. Over 90% of the healthy subjects and about 70% of the patients could not describe any services where they would feel comfortable discussing mental health problems. In both groups, “adolescents and young adults” were ranked first as a target population for mental health and illness policies. The top requirement for the integrated care systems was the promotion and awareness of correct knowledge of mental illness in both the healthy subjects and patients. Conclusion Societal requirements could include disseminating correct knowledge, awareness-raising actions for society, and implementing services where people, especially young people, can easily consult and receive support in the community.